KORELASI KONSENTRASI TEPUNG KACANG KORO PEDANG (Canavalia ensiformis L.) TERMODIFIKASI TERHADAP KARAKTERISTIK PRODUK COOKIES - Widiantara, Tantan Widiantara; Ghaffar, Rizal Maulana Ghaffar; Asep Dedy Sutrisno; Cindy Zahra Putri Hermawan; Apriani Widiya Zakiyyatunnisa (Pasundan Food Technology Journal (PFTJ), 2025)
This study aims to determine the correlation between the concentration of modified sword bean (Canavalia ensiformis L.) flour and the characteristics of cookies. The research was conducted in two stages. In the first stage, modified sword bean flour was produced through fermentation using Lactobacillus plantarum. In the second stage, cookies were prepared with varying concentrations of the modified flour, followed by chemical, physical, and consumer acceptance analyses. Simple linear regression was applied, with the independent variable being the concentration of modified sword bean flour (0%, 10%, 20%, 30%, 40%, and 50%), and the dependent variables being the chemical and physical characteristics. Meanwhile, sensory response data were analyzed using Analysis of Variance (ANOVA). The results showed that the concentration of modified sword bean flour had a very strong positive correlation with protein content (r = 0.9452), a very strong negative correlation with carbohydrate content (r = -0.9408), a strong negative correlation with fat content (r = -0.6697), a very strong positive correlation with moisture content (r = 0.8665), a very strong negative correlation with ash content (r = -0.9398), a very strong negative correlation with pH value (r = -0.8736), and a very strong negative correlation with hardness (r = -0.9528). Consumer acceptance tests revealed that the color attribute achieved the highest score at a 20% concentration, aroma and aftertaste received the highest ratings at 0% concentration (control), while taste and texture scored highest at a 10% concentration.